Fasting Leptin Is a Metabolic Determinant of Food Reward in Overweight and Obese Individuals during Chronic Aerobic Exercise Training - Mark Hopkins; Catherine Gibbons; Phillipa Caudwell; Dominic-Luc Webb; Per M. Hellström; Erik Näslund; John E. Blundell; Graham Finlayson (International Journal of Endocrinology)
Changes in food reward have been implicated in exercise-induced compensatory eating behaviour. However, the underlying mechanisms of food reward, and the physiological correlates of exercise-induced changes in food reward, are unknown. Methods. Forty-six overweight and obese individuals completed 12 weeks of aerobic exercise. Body composition, food intake, and fasting metabolic-related hormones were measured at baseline, week six, and postintervention. On separate days, the reward value of high-and-low-fat food (explicit liking and implicit wanting) was also assessed at baseline, week six, and postintervention. Results. Following the intervention, FM, FFM, and VO2peak improved significantly, while fasting leptin decreased. However, food intake or reward did not change significantly. Cross-sectional analyses indicated that FM (P=0.022) and FFM (P=0.046) were associated with explicit liking for high-fat food, but implicit wanting was associated with FM only (P=0.005). Fasting leptin was associated with liking (P=0.023) and wanting (P=0.021) for high-fat food. Furthermore, a greater exercise-induced decline in fasting leptin was associated with increased liking (P=0.018). Conclusion. These data indicate that food reward has a number of physiological correlates. In particular, fasting leptin appears to play an active role in mediating food reward during exercise-induced weight loss.